HUBUNGAN FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN GANGGUAN PENDENGARAN AKIBAT BISING PADA PEKERJA WELDER DI PT. â€œXâ€ - Susanti, Rini; Rusdani, Rusdani; Famelia, Fibri (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2021)
PT. â€œXâ€ is an industry works in fabrication of freight oil construction services. This industry used machines which produce overwhelming noises that surpass threshold value 85 dB(A). The purpose of this research is to determine the influence of the noise intensity toward the Noise Induced Hearing Loss (NIHL). NIHL is a type of sensorineural hearing loss caused by exposure to loud sound in a long term. NIHL influenced by several factors such as noise intensity, duration of exposure, period of employment and hearing protection equipment. This study aims to determine the relationship of noise intensity, duration of exposure, period of employment and hearing protection equipment with NIHL. The design of this research was quantitative with cross-sectional approach, using total sampling sample technique. The total sample for this research is 75 respondens. Data obtained through the measurement data of the noise intensity on a regular basis by HSE PT. â€œXâ€, medical check-up and questionnaire, the analysis test using the chi-square test. From the result of this research noise intensity, duration of exposure and period of employment have a significant relationship with NIHL, while hearing protection equipment have no significant relationship with NIHL. The chi-square test result shows that the p-value for noise intensity is 0.001, duration of exposure is 0.005, period of work 0.023 and hearing protection equipment 0,121.There is a significant relationship on the correlation of noise intensity, duration of exposure, and period of employment with NIHL and there is no significant relationship between hearing protection equipment with NIHL.Â